BIOLOGICAL NITROGEN FIXATION AND ITS EFFECTS ON THE PHYSIOLOGICAL POTENTIAL OF COMMON BEAN SEEDS - Mondo, Vitor Henrique Vaz; Ferreira, Enderson PetrÃ´nio de Brito; Fageria, Nand Kumar; Costa, Marco TÃºlio Machado (REVISTA DE AGRICULTURA, 2014)
The aim of this study was to evaluate the effects of biological nitrogen fixation and its association with mineral sources of nitrogen in common bean seed physiological potential. One concluded that the mineral nitrogen fertilization, for common bean crop, when associated with biological nitrogen fixation, may be reduced from high (120 kg.ha-1 of N) to low doses (50 kg.ha-1 of N).Â Such reduction does not affect seed physiological potential.